PENGARUH GAME BASED LEARNING BERBANTUAN PROPROFS BRAIN GAMES TERHADAP LEARNING ENGAGEMENT SISWA SEKOLAH DASAR - Amalia, Natasya; Fitri, Ayu; Widiastuti, Hesti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Student learning engagement in mathematics learning in elementary schools is still relatively low due to the dominance of conventional learning models that are less participatory. This study aims to examine the effect of the Game Based Learning (GBL) model assisted by ProProfs Brain Games on learning engagement in mathematics learning of fifth-grade students of SDN Cikampek Utara II. The research method used is quantitative with a quasi-experimental design of the nonequivalent control group design. The study population included all 100 students of SDN Cikampek Utara II, with a sample of 48 fifth-grade students selected through certain techniques and divided into an experimental group of 24 students and a control group of 24 students. The data collection instrument questionnaire a pretest-posttest that measured three dimensions of engagement: cognitive, behavioral, and emotional. Data analysis was carried out using an independent sample t-test at a significance level of 0.05. The results showed that the GBL model assisted by ProProfs Brain Games had a significant effect on student learning engagement with a significance value of 0.000 (p <0.05). The experimental group's average posttest score reached 76.21, significantly higher than the control group's score of 61.00. In conclusion, this digital game-based learning approach is effective in enhancing all three dimensions of student engagement, making it worthy of consideration as an innovative alternative for mathematics learning in elementary schools.